Adaptasi Pembelajaran Seni Budaya Berbasis Kolaboratif Masyarakat Pada Masa Darurat Covid 19 - ceceng kosasih (Magelaran: Jurnal Pendidikan Seni, 2021)
This article is the result of a study of the learning system developed during the emergency of the COVID-19 pandemic. The concept of collaborative learning with the community is an alternative and is allegedly able to complement the deficiencies in the distance learning process carried out with online, offline or semi-network systems. , with various obstacles it faces.